Butterfly hug intervention and anxiety among preoperative odontectomy patients - Faizar Dimas Nugraha; Cahaya Nugraheni; Heri Puspito (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Odontectomy under general anesthesia frequently triggers pre-operative anxiety, which carries the risk of causing physiological complications and even surgical cancellation. Management that relies solely on pharmacological premedication can produce adverse side effects, making it necessary to explore safe and practical self-administered relaxation alternatives. One such non-pharmacological therapy for managing this anxiety is the butterfly hug technique. Purpose: To explore the effectiveness of butterfly hug therapy as a practical and structured self-administered non-pharmacological relaxation intervention in reducing anxiety levels among pre-operative odontectomy patients. Method: A quantitative approach with a pre-experimental research design was used. Samples were selected through purposive sampling, yielding 44 respondents. Data were collected using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. Data analysis was performed using the non-parametric Wilcoxon Signed-Rank Test. Results: The bivariate Wilcoxon test yielded a significance value of 0.000, which is lower than 0.05 (sig. 0.000 < 0.05), indicating a significant difference between pre-test and post-test scores. The hypothesis stating that